2013
DOI: 10.1107/s1744309113014152
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization reports are the backbone ofActa Cryst. F, but do they have any spine?

Abstract: Crystallization of macromolecules is famously difficult. By knowing what has worked for others, researchers can ease the process, both in the case where the protein has already been crystallized and in the situation where more general guidelines are needed. The 264 crystallization communications published in Acta Crystallographica Section F in 2012 have been reviewed, and from this analysis some information about trends in crystallization has been gleaned. More importantly, it was found that there are several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…The impact that this screen had on protein crystallization is tremendous and cannot be adequately conveyed by the >2000 citations that the publication has thus far received. Not only has it been very effective at crystallizing proteins, as seen by the fact that it is still one of the most widely used screens today, even in a crowded field of over 200 commercially available screens (Newman et al, 2013), but also it lowered the barrier to crystallization. The sparse-matrix screen was a constant, making it well suited for automation.…”
Section: The First Crystallization 'Kit'mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact that this screen had on protein crystallization is tremendous and cannot be adequately conveyed by the >2000 citations that the publication has thus far received. Not only has it been very effective at crystallizing proteins, as seen by the fact that it is still one of the most widely used screens today, even in a crowded field of over 200 commercially available screens (Newman et al, 2013), but also it lowered the barrier to crystallization. The sparse-matrix screen was a constant, making it well suited for automation.…”
Section: The First Crystallization 'Kit'mentioning
confidence: 99%
“…In some cases the initial crystallization-screening experiment may produce a crystal that can be directly used to yield a model of the structure. However, more typically the production of X-ray-quality crystals occurs via optimization (Newman et al, 2013). Optimization makes use of the information obtained from initial screening to develop strategies and crystallization cocktails which focus more narrowly on areas of crystallization space that are likely to produce crystals.…”
Section: Optimizationmentioning
confidence: 99%
“…Therefore, our 'winning' screen for the shotgun approach to crystallization may be successful because it was set up a lot or because it has a good overlap with many of the screens that were set up a lot. Given the similarity between the 'top ten' most successful screens by condition, we suspect that the most successful screen from our analysis (MCSG_1) just happens to contain the highest number of conditions from the NR-SCC; other work has not suggested that this screen is particularly widely used (Newman et al, 2013). One institute where the MCSG_1 screen is certainly used is the Midwest Center for Structural Genomics (http://www.mcsg.anl.gov/), from whence the screen came.…”
Section: Discussionmentioning
confidence: 96%
“…Most diffraction-quality crystals do not grow directly from screening conditions (Newman et al, 2013), and one or more cycles of optimization have to be performed. In this case, the goal of the initial screening is to get close enough to a crystal that a condition can be recognized as being a lead, and optimization techniques can then finish the process.…”
Section: Discussionmentioning
confidence: 99%
“…In July this year, we published a contribution by Janet Newman and colleagues entitled Crystallization reports are the backbone of Acta F, but do they have any spine? (Newman et al, 2013;Weiss & Einspahr, 2013). The central message of this paper was that the information content of crystallization communications published in Acta Cryst.…”
mentioning
confidence: 99%